Comparative Analysis of the Legal Regulation of Civil Liability for Harm Caused to Human Life and Health - O. B. Shubina; K. A. Filippova (Евразийская интеграция: экономика, право, политика, 2020)
The purpose of this article is a comparative analysis of the legal regulation of civil liability for harm caused to human life and health by activities that create an increased danger to others in Russia and foreign countries. Due to the intensive development of new technologies and the emergence of new sources of increased danger, there is a need to specify the concept of «activities that create increased danger to others» in Russian legislation. The subject of the article is the norms of law of Russian and foreign legislation regulating the institution of civil liability for harm caused to human life and health by activities that create an increased danger to others. The article is written using General scientific, philosophical and special legal methods of cognition. Based on the results, the article assesses the specifics of regulating harm caused by activities that create an increased danger to others in foreign legislation. Based on the research, it is proposed to distinguish the concepts of «source of increased danger» and «activities that are associated with increased danger to others» in Russian legislation, adding a note to article 1079 of the Civil code of the Russian Federation, as well as to specify the list of sources of increased danger, including unmanned vehicles and fighting dogs.